Respuesta :
We need to find value of x from the equation, so let write the equation first;
[tex]{:\implies \quad \sf \dfrac{7x+14}{3}-\dfrac{17-3x}{5}=6x-\dfrac{4x+2}{3}-5}[/tex]
Taking LCM both sides ;
[tex]{:\implies \quad \sf \dfrac{35x+70-(51-9x)}{15}=\dfrac{18x-(4x+2)-15}{3}}[/tex]
Multiplying both sides by 15 and simplifying ;
[tex]{:\implies \quad \sf 35x+70-51+9x=5(18x-4x-2-15)}[/tex]
[tex]{:\implies \quad \sf 44x+19=5(14x-17)}[/tex]
[tex]{:\implies \quad \sf 44x+19=70x-85}[/tex]
[tex]{:\implies \quad \sf 70x-44x=19+85}[/tex]
[tex]{:\implies \quad \sf 26x=104}[/tex]
[tex]{:\implies \quad \sf x=\dfrac{104}{26}=\boxed{\bf 4}}[/tex]
Hence, The required answer is 4
Given: {(7x + 14)/3} - {(17 - 3x)/5} = 6x - {(4x + 2)/3} - 5
Asked: Find the value of x = ?
Explanation: Given equation is {(7x + 14)/3} - {(17 - 3x)/5} = 6x - {(4x + 2)/3} - 5
⇛{(7x + 14)/3} - {(17 - 3x)/5} = {(6x)/1} - {(4x + 2)/3} - (5/1)
⇛{(7x*5 + 14*5 - 17*3 + 3x*3)/15} = {(6x*3 - 4x*1 - 2*1 - 5*3)/3}
⇛{(35x + 70 - 51 + 9x)/15} = {(18x - 4x - 2 - 15)/3}
⇛{(35x + 9x + 70 - 51)/15} = {(18x - 4x - 2 - 15)/3}
⇛{(44x + 19)/15} = {(14x - 17)/3}
⇛[{1/15}(44x + 19)] = [{1/3}(14x - 17)}]
⇛{(44x + 19)/15} = {(14x - 17)/3}
Since (a/b) = (c/d) ⇛a(d) = b(c) ⇛ad = bc
Where, a = 44x + 19, b = 15
c = 14x - 17 and d = 3
On applying cross multiplication then
⇛3(44x + 19) = 15(14x - 17)
Multiply the numbers outside of the bracket with numbers in the bracket.
⇛132x + 57 = 210x - 255
Shift the variable value on LHS and constant value on RHS.
⇛132x - 210x = -255 - 57
Subtract the values on LHS and RHS.
⇛(-78x) = (-312)
Shift the number (-78) from LHS to RHS.
⇛x = {(-312)/(-78)
Simplify the RHS fraction to get the final value of x.
⇛x = 4/1
Therefore, x = 4
Answer: Hence, the value of x for the given problem is 4.
EXPLORE MORE:
Verification:
Check whether the value of x for the given problem is true or false.
If x = 4 then LHS of the equation is
{(7x + 14)/3} - {(17 - 3x)/5}
= [{7(4) + 14}/3] - [{17 - 3(4)}/5]
= {(7*4 + 14)/3} - {(17 - 3*4)/5}
= {(28 + 14))3} - {(17 - 12)/5}
= (42/3) - (5/5)
= (42/3) - 1
= (42/3) - (1/1)
= {(42 - 1*3)/3
= {(42 - 3)/3}
= (39/3)
= 13/1
= 13
And RHS = 6x - {(4x + 2)/3} - 5
= 6(4) - [{4(4) + 2}/3] - 5
= 24 - {(16 + 2)/3} - 5
= 24 - (18/3) - 5
= 24 - (6/1) - 5
= (24/1) - (6/1) - (5/1)
= (24*1 - 6*1 - 5*1)/1
= (24 - 6 - 5)/1
= (24 -11)/1
= 13/1
= 13
On comparing with both the sides, we notice that LHS = RHS is true for x = 4
Hence, verified.
also read similar questions: Solve 5/6 (4x + 8) = 3/8 x - 1/4 using algebraic operations.
Solve the equation: 5(3p - 5) + 4p = 5p - 6( p + 4)....
https://brainly.com/question/26031869?referrer